2010
DOI: 10.1016/j.neuroimage.2010.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the validity of volume-based and surface-based brain image registration for developmental cognitive neuroscience studies in children 4 to 11years of age

Abstract: Structural and functional magnetic resonance imaging (fMRI) has been used increasingly to investigate typical and atypical brain development. However, in contrast to studies in school-aged children and adults, MRI research in young pediatric age groups is less common. Practical and technical challenges occur when imaging infants and children, which presents clinicians and research teams with a unique set of problems. These include procedural difficulties (e.g., participant anxiety or movement restrictions), te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
190
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(198 citation statements)
references
References 48 publications
(65 reference statements)
5
190
1
2
Order By: Relevance
“…As described in Methods, our tractography method relies on the segmentation of each participant's T1-weighted structural scan within FreeSurfer, a process that was originally based on adult participants. However, previous work has demonstrated that this method is robust and unbiased when tested on children in the same age range as those in the preent study (31). Further, because our tractography method uses information from the atlas about which anatomical labels each tract passes through or next to, and not about the exact spatial location or shape of the tract, it does not require perfect spatial alignment of study subjects to the atlas.…”
Section: Discussionmentioning
confidence: 99%
“…As described in Methods, our tractography method relies on the segmentation of each participant's T1-weighted structural scan within FreeSurfer, a process that was originally based on adult participants. However, previous work has demonstrated that this method is robust and unbiased when tested on children in the same age range as those in the preent study (31). Further, because our tractography method uses information from the atlas about which anatomical labels each tract passes through or next to, and not about the exact spatial location or shape of the tract, it does not require perfect spatial alignment of study subjects to the atlas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-analysis has confirmed a connection between the size of the hippocampus and memory performance during brain development in children and young adults (Van Petten, 2004). Overall, the research evidence suggests that cognitive development is strongly connected with micro and macro-anatomical changes which take place throughout childhood (Levitt, 2003;Herlenius and Lagercrantz, 2004;Ghosh et al, 2010). Individual brain development follows a genetic program which is influenced by environmental factors including nutrition (Bryan et al, 2004;Toga et al, 2006;Giedd et al, 2010).…”
Section: Brain Development In Humansmentioning
confidence: 95%
“…We additionally performed a surface-based vertex-wise analysis of between-group cortical thickness differences in order to preserve spatial specificity. First, data from each subject was resampled to a standard space with the MNI305 template; this has been validated in children previously (21). Next, each dataset was spatially smoothed using a 15 mm full-width at half maximum (FWHM) Gaussian kernel along the cortical surface (22).…”
Section: Mri Analysis and Anatomic Classificationmentioning
confidence: 99%